2022
DOI: 10.1038/s41598-022-15739-w
|View full text |Cite
|
Sign up to set email alerts
|

Vascular calcification in different arterial beds in ex vivo ring culture and in vivo rat model

Abstract: Vascular calcification is a risk factor for cardiovascular and kidney diseases. Medial calcification may differently affect the arterial tree depending on vessel location and smooth muscle injury. The aim was to map the anatomical distribution of vascular calcifications on different arteries and artery locations, in cultured artery rings (ex vivo) and in a rat model of elastocalcinosis (in vivo). Vascular calcification was assessed histologically (von Kossa staining of the media) and by calcium content measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In conclusion, the requirement for FBS is not constant: CJ cells showed a distinct FBS requirement in CaP-ppt formation (Figure 4). Similar FBS-dependent CaP-ppt formation has been reported in an ex vivo organ culture system with 3.8 mM β-GP-added rat aortic rings [44,45]. On the contrary, it has been reported that FBS suppresses calcification in planar culture systems of rat VSMCs [26] or human VSMCs [44] with β-GP added.…”
Section: -7: Anti-cap-ppt Action Of Bisphosphonatessupporting
confidence: 73%
See 1 more Smart Citation
“…In conclusion, the requirement for FBS is not constant: CJ cells showed a distinct FBS requirement in CaP-ppt formation (Figure 4). Similar FBS-dependent CaP-ppt formation has been reported in an ex vivo organ culture system with 3.8 mM β-GP-added rat aortic rings [44,45]. On the contrary, it has been reported that FBS suppresses calcification in planar culture systems of rat VSMCs [26] or human VSMCs [44] with β-GP added.…”
Section: -7: Anti-cap-ppt Action Of Bisphosphonatessupporting
confidence: 73%
“…The solution pH problem during calcification is then discussed. In general, there is a traditional view of the EC phenomenon as a cellular degenerative, passive process and a newer view as an active, proactive process mediated by cellular metabolism [45]. The most widely used experimental system for CVC is the combination of primary cultures of arterial smooth muscle or valve stromal cells with high concentrations of phosphoric acid [19].…”
Section: Discussionmentioning
confidence: 99%
“…Segment-specific distribution of heterogeneous VSMCs likely contributes significantly to aortic disease characteristics. Further support for this view is the fact that the aortic arch, which is composed of CNC-derived VSMCs, is the segment of the thoracic aorta that is more susceptible to calcification [45,46]. As VSMCs of different embryonic origins have heterogeneous patterns in response to environmental cues, genetic mutations that can affect intracellular signaling could also have heterogeneous effects on them.…”
Section: Vsmc Phenotypic Diversity In Hereditary Aasmentioning
confidence: 99%
“…Therefore, to study the underlying mechanisms of atherosclerosis and to develop treatments, the following research models have been applied; in vitro models using cultured cells [8,9]; ex vivo models using animal blood vessels [10]; and in vivo models using genetically modified animals or disease model animals with feeding, substance application, or kidney removal [11]. However, the existing atherosclerosis study models have several issues.…”
Section: Introductionmentioning
confidence: 99%